"Nobody Loves a Fat Man": Masculinity and Food in Film Noir. (October 2013) - Forth, Christopher E.
This article uses the proverb "nobody loves a fat man" to examine the interplay between representations of masculinity, physique, and "appetite" in American culture during the first half of the twentieth century, with special attention to depictions of fat characters in Hollywood thrillers designated as "film noir." By emphasizing how fluidly the concept of "appetite" facilitated connections between the sexual and the culinary, it argues that fat criminals in film noir embody long-standing yet contradictory ideas about manhood, consumption, and desire. To support this claim, the article (1) explicates film noir as a site for examining the instability of masculinity; (2) probes the historical background to perceptions of fat males as weak, impulsive, and perverse; (3) examines representations of fat criminals in select films noirs; and (4) reveals cinematic instances where the virtues of male domesticity smoothed out the perceived incongruence between manhood and fatness.